Active braking control of two-wheeled vehicles on curves. (17th May 2010) - Tanelli, Mara; Corno, Matteo; Boniolo, Ivo; Savaresi, Sergio M.
This paper focuses on the design of an innovative active braking control system for two-wheeled vehicles which can handle panic braking on curves. In the field of two-wheeled vehicles the spread of electronic control systems its still in its infancy, as today only a few commercial motorbikes are equipped with Anti-lock Braking Systems (ABS). Moreover, the few ABS systems available are certified to work only when panic braking occurs on straight road. As will be shown, to guarantee safety when braking on curves, the designed controller needs to rely on an online measure of the vehicle roll angle. Thus, to prove the industrial applicability of the proposed control algorithm, we also describe how such quantity can be effectively estimated via a suitable algorithm based on a low-cost sensors configuration, whose effectiveness is assessed in simulation and also on an instrumented test vehicle. The results concerning the active braking control system will be tested on a very detailed multibody simulation model of a two-wheeled vehicle, MSC BikeSim®.